Exogenous control over intracellular acidification: Enhancement via proton caged compounds coupled to gold nanoparticles and an alternative pathway with DMSO - Carbone, Marilena; SABBATELLA, GIANFRANCO; Antonaroli, Simonetta; Remita, Hynd; ORLANDO, Viviana; BIAGIONI, Stefano; NUCARA, Alessandro (Data in Brief, 2016)
Proton caged compounds exhibit a characteristic behavior when directly dosed into cells or being coupled to gold nanoparticles prior to the dosing. When irradiated in the near ultraviolet region, they release protons that interact with intracellular HCO3 to yield H2CO3. The dissociation of carbonic acid, then, releases CO2 that can be distinctively singled out in infrared spectra. In the process of searching a pathway to augment the intracellular uptake of proton caged compounds, we probed the association of 1-(2-nitrophenyl)-ethylhexadecyl sulfonate (HDNS) with DMSO, an agent to enhance the membrane permeability. We found out a different UV-induced protonation mechanism that opens up to new conduits of employing of proton caged compounds. Here, we report the infrared data we collected in this set of experiments.